“Let’s Walk My Journey”: Securitization of Refugee Issues in Indonesia through Works of Art (pp. 17-54) - Alessandro Kurniawan Ulung; Clemontin Cornelia Monica Jannah (JURNAL KEAMANAN NASIONAL, 2023)
This study aims to research securitization carried out by RDI Urban Refugee Research Group (RDI UREF) through art exhibition Let’s Walk My Journey in 2022. The group used works of art to securitize human security issues faced by refugees in transit in Indonesia. The issues ranged from uncertain resettlement in a third country to the lack of human rights access to get legal employment and education in Indonesia. This study used a qualitative method, with the theory of securitization by Barry Buzan and Ole Wæver in place. The author found that UREF’s securitization sought to draw the attention of the Indonesian public in a bid to make them aware of refugee issues. The group expected the bigger public awareness to become a stronger force in urging the government to ensure refugees’ rights. Let’s Walk My Journey allowed UREF to become a securitization actor, with refugees in transit as a referent object and the Indonesian people and government as a targeted audience. In the exhibition, the group used artworks as speech acts to make the public and government realize that refugee issues were an existential threat that they need to address and solve together for the sake of humanity.